Pendekatan Semantik Alquran Tosihiko Izutsu: Altrnatif Memahami Maksud Alquran Tanpa Intimidasi Makna - Muhammad Aly Mahmudi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2022)
and will not even stop to be studied. The exploitation of science from it does not only stop among Muslim scholars, even Orientalists are very amazed and amazed to see the potential in the Quran. Tosihiko Izutsu is one of the Japanese orientalists who tries to study the meaning of the Qur'an by mnegusung semantic jargon to bring out the meaning in the quran without intimidating the meaning that is desired by apalagai following the intention of the eater or interpreter. In this study, the researcher used the study of the Literature study by collecting data from various sources to express Izutsu's thoughts in revealing the meaning of the Quran. By giving the first conclusion: the meaning in the koran cannot be forced into fulfilling the original message conveyed secondly: the semantic method offered by Izutsu is very relevant to find the meaning offered by the koran.